PEMANFAATAN WEBSITE SEBAGAI MEDIA PENGEMBANGAN LOYALITAS WALI MURID DI MADRASAH IBTIDAIYAH MUHAMMADIYAH PASIRMUNCANG - Wainah Wainah (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
The website is familiar in the world of education, most schools have implemented it as a means of communication between internal parties and external parties (student guardians). Website can be used anytime, anywhere can be accessed to convey something related to school activities or programs. This site helps school management in data management and processing and also makes it easy to quickly, precisely, and effectively analyze information. Website as well as a school public relations. The purpose of this study is to provide an overview or describe the use of the website as a medium for the development of Walimurid loyalty in MI Muhammadiyah Pasirmuncang. This research is a qualitative descriptive research approach with a type of phenemonology. As for the Subjects are the Principal, Teacher and Walimurid, while the data collection techniques are by interview, observation and documentation, while the data analysis uses data reduction, data presentation and conclusions. The results of research that has been carried out at MI Muhammadiyah Pasirmuncang is the use of the website as a medium of communication with internal and external parties.